EVALUATION OF ETHANOLIC ROOT EXTRACT OF PARTHENIUM HYSTEROPHORUS LINN FOR ANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITY - Lohumi, Pankaj; Kumar, Tirath; Nogai, Lipi (International Journal of Current Pharmaceutical Research, 2017)
Objective: The work is aimed to draw out the health beneficial properties of a weed (Parthenium hysterophorus Linn). The present work is organized to evaluate the antioxidant and anti-inflammatory activity of the ethanolic root extract of Parthenium hysterophorus Linn. Methods: In the present work the ethanolic extract was determined by using soxhlet apparatus. The antioxidant scavenging activity of this extract was determined by applying three different assay methods: (1) DPPH (1, 1-diphenyl-2-picryl hydrazyl) free radical method. (2) Nitric oxide scavenging assay and (3) Reducing power method. The anti-inflammatory activity was determined by in vivo method i.e. Carrageenan induced rat paw edema. Results: DPPH radical scavenging activities of the standard antioxidant and extracts were found to be increased in dose dependent manner. The percentage inhibition increases from 4.19% to 97.09% within the concentration range of 10µg/ml to 160µg/ml. Parthenium hysterophorus Linn effectively reduced the generation of nitric oxide radicals from sodium nitroprusside solution in a concentration dependent manner and percentage inhibition increases from 3.53% to 55.21% within the concentration range 10µg/ml to 160µg/ml. All the concentrations of extract significantly showed higher absorbance than the absorbance of control reaction (0.9705) in reducing power assay. A Higher absorbance indicates high reducing power due to the formation of reduced intermediates. Parthenium hysterophorus Linn showed highly significant anti-inflammatory activity at a dose of 200 mg/kg and the lesser effect was observed at 100 mg/kg with the percentage change in paw volume at 0 min, 30 min, 60 min, 90 min and 120 min. Conclusion: Thus, from above experimental observations, it can be stated that Parthenium is a natural antioxidant and bearing anti-inflammatory activity.